UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BUAH KABAU (Archidendron bubalinum) TERHADAP Staphylococcus aureus - Oktiarni, Dwita; Gaol, Amelia Debora Lumban; Avidlyandi; Gustian, Irfan; Putranto, Agus Martono Hadi (UNIB Press, 2025)
The kabau plant (Archidendron bubalinum) is an endemic plant of Indonesia, especially on the island of Sumatra, with secondary metabolite content in the form of flavonoids, tannins, saponins and steroids which have antimicrobial activity. This study aims to determine the antibacterial activity of ethanol extract of kabau fruit peels (Archidendron bubalinum) against Staphylococcus aureus and to determine the optimum percentage of extract in inhibiting Staphylococcus aureus with percentages 1%, 2.5%, 5% and 10%. The antibacterial activity of kabau fruit peels extract was tested by the well diffusion method using Nutrient Agar (NA) media. The results showed that ethanol extract of kabau fruit peels with a percentage of 10% was the optimum percentage in inhibiting the growth of Staphylococcus aureus with an inhibition zone diameter of 10.59 mm. From the data, it can be concluded that the extract of kabau fruit peels has the potential as an antibacterial against Staphylococcus aureus with a sensitive inhibitory category.